MANAGEMENT OF ENDOCRINE DISEASE: Novel anabolic treatments for osteoporosis. Issue 2 (February 2018) - Canalis, Ernesto
Abstract : Skeletal anabolic agents enhance bone formation, which is determined by the number and function of osteoblasts. Signals that influence the differentiation and function of cells of the osteoblast lineage play a role in the mechanism of action of anabolic agents in the skeleton. Wnts induce the differentiation of mesenchymal stem cells toward osteoblasts, and insulin-like growth factor I (IGF-I) enhances the function of mature osteoblasts. The activity of Wnt and IGF-I is controlled by proteins that bind to the growth factor or to its receptors. Sclerostin is a Wnt antagonist that binds to Wnt co-receptors and prevents Wnt signal activation. Teriparatide, a 1–34 amino terminal fragment of parathyroid hormone (PTH), and abaloparatide, a modified 1–34 amino terminal fragment of PTH-related peptide (PTHrp), induce IGF-I, increase bone mineral density (BMD), reduce the incidence of vertebral and non-vertebral fractures and are approved for the treatment of postmenopausal osteoporosis. Romosozumab, a humanized anti-sclerostin antibody, increases bone formation, decreases bone resorption, increases BMD and reduces the incidence of vertebral fractures. An increased incidence of cardiovascular events has been associated with romosozumab, which is yet to be approved for the treatment of osteoporosis. In conclusion, cell and molecular studies have formed the foundation for the development of new anabolic therapies for osteoporosis with proven efficacy on the incidence of new fractures.